Protective effect of rutin on mercuric chloride‐induced reproductive damage in male rats. (5th February 2020) - Kandemir, Fatih Mehmet; Caglayan, Cuneyt; Aksu, Emrah Hicazi; Yildirim, Serkan; Kucukler, Sefa; Gur, Cihan; Eser, Gizem
Abstract: This study investigated the effects of rutin against reproductive damage caused by toxic mercury in male rats. Thirty‐five Sprague Dawley rats were used. Control group was injected with saline for 7 days. The rutin‐100 group received 100 mg/kg/b.w. rutin for 7 days. Mercuric chloride (HgCl2 ) group received 1.23 mg/kg/b.w. of HgCl2 for 7 days. Mercury chloride + rutin‐50 group received 50 mg/kg/b.w. rutin and HgCl2 1.23 mg/kg/b.w. for 7 days. HgCl2 + rutin‐100 group received 100 mg/kg/b.w. rutin and HgCl2 1.23 mg/kg/b.w. for 7 days. It was detected that HgCl2 treatment increased malondialdehyde (MDA) levels, tumour necrosis factor‐α (TNF‐α) and cyclooxygenase‐2 (COX‐2) expressions, necrosis and degeneration of spermatogonium, dead and abnormal sperm percentages; tubular walls thinning; and decreased antioxidant enzyme activities and sperm motility. It was determined that rutin application reduced testicular damage caused by HgCl2 . In conclusion, rutin administration may treat HgCl2 toxicity in testes.